High-thermal-conductivity epoxy adhesive for chip packaging and chip packaging method
By using polyethylene glycol-grafted epoxy resin and polyamide-coated nanofillers in the epoxy adhesive for chip packaging, the problem of insufficient thermal conductivity and mechanical strength of epoxy adhesives in the prior art is solved, and the effects of high thermal conductivity and high mechanical strength are achieved, thereby improving the quality of chip packaging.
Patent Information
- Application Number
- CN202411761921.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-28
AI Technical Summary
The existing epoxy adhesives for chip packaging have shortcomings in thermal conductivity and mechanical strength, resulting in low chip packaging quality.
The nanofiller coated with polyethylene glycol grafted epoxy resin and polyamide are further optimized by the polyethylene glycol grafting reaction and the formation of polyamide coating layer.
The thermal conductivity and mechanical strength of the epoxy adhesive for chip packaging are significantly improved, and the quality of chip packaging is improved.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of chip packaging, and in particular to an epoxy adhesive for chip packaging with high thermal conductivity and a chip packaging method. Background Art
[0002] In the chip packaging process, epoxy adhesive plays a vital role as a key material. Epoxy adhesive not only needs to provide strong adhesion, but also needs to have good thermal conductivity, chemical corrosion resistance and electrical properties to ensure the reliable operation of the chip in various complex environments.
[0003] In the related art, an epoxy adhesive for chip packaging is disclosed. The components of the epoxy adhesive are, by mass, 15-20 parts of biseugenol epoxy resin, 5-10 parts of poly(dodecanediamine) terephthalamide, 1-5 parts of polythiol, 0.5-1.0 parts of imidazole, 20-30 parts of isopropylphenoxy functionalized boron nitride nanosheets, and 10-15 parts of carbon nanotubes.
[0004] Although isopropylphenoxy-functionalized boron nitride nanosheets and carbon nanotubes can improve the thermal conductivity of epoxy adhesives, if they are not dispersed evenly, they will form agglomerates, which will not only fail to ensure thermal conductivity, but also cause stress concentration inside the colloid, reduce its mechanical strength, and thus lead to low quality of chip packaging. Summary of the invention
[0005] In order to improve the chip packaging quality, the present application provides a high thermal conductivity epoxy adhesive for chip packaging and a chip packaging method.
[0006] In a first aspect, the present application provides a high thermal conductivity epoxy adhesive for chip packaging, which adopts the following technical solution:
[0007] A high thermal conductive epoxy adhesive for chip packaging comprises a component A and a component B. Calculated by the total weight of the component A, the component A comprises the following raw materials in parts by weight: 28-44 parts of polyethylene glycol grafted epoxy resin, 15-20 parts of polyamide-coated nanofiller, 4-7 parts of flame retardant, 3-4 parts of diluent, and 12-15 parts of toughening agent. The component B comprises an epoxy curing agent and a curing accelerator in a weight ratio of 10:(0.5-1).
[0008] By adopting the above technical scheme, the polyethylene glycol segment is introduced into the epoxy resin molecular chain, which can reduce the interfacial tension of the epoxy resin and improve the compatibility of the epoxy resin and the nanofiller. The nanofiller can improve the thermal conductivity of the epoxy adhesive. The polyamide coating layer can effectively prevent the mutual approach and agglomeration between the nanofillers through the steric hindrance effect and the electrostatic repulsion, and enhance the compatibility of the nanofiller with the epoxy resin, and keep the nanofiller uniformly dispersed in the epoxy resin. Flame retardant, diluent and toughening agent. The flame retardant property, processing performance and toughness of the epoxy adhesive can be improved. Therefore, by adopting the above raw materials, the dispersibility of each component inside the epoxy adhesive for chip packaging can be improved, so that the epoxy adhesive has good thermal conductivity and mechanical system performance, which helps to improve the chip packaging quality.
[0009] In a specific embodiment, the polyethylene glycol grafted epoxy resin comprises the following raw materials: 15-25 parts of epoxy resin, 5-10 parts of polyethylene glycol, 1-2 parts of organic tin catalyst, and 40-50 parts of acetone.
[0010] By adopting the above technical scheme, the epoxy resin and the polyethylene glycol are dispersed in acetone, and under the catalytic action of the organic tin catalyst, the epoxy resin and the polyethylene glycol undergo a grafting reaction to obtain the polyethylene glycol-grafted epoxy resin.
[0011] In a specific embodiment, the preparation method of the polyethylene glycol grafted epoxy resin comprises the following steps:
[0012] Weigh epoxy resin, polyethylene glycol, organotin catalyst and acetone according to proportion;
[0013] First, epoxy resin and acetone are mixed, polyethylene glycol is added, and the mixture is stirred evenly at 60-80°C. An organic tin catalyst is added, and under continuous stirring at 110-140°C, the polyethylene glycol and epoxy resin undergo a ring-opening grafting reaction. After the reaction is completed, a polyethylene glycol-grafted epoxy resin is obtained.
[0014] By adopting the above technical solution, the epoxy resin is first mixed with acetone, which can reduce the viscosity of the epoxy resin and facilitate subsequent operations. Under continuous stirring and the above reaction temperature, it is helpful to increase the reaction rate and uniformity, thereby further improving the compatibility of the epoxy resin and the filler.
[0015] In a specific embodiment, the polyamide-coated nanofiller comprises the following raw materials: 10-15 parts of nanofiller, 10-15 parts of polyamide resin, and 30-40 parts of N-methylpyrrolidone.
[0016] By adopting the above technical solution, the polyamide resin and the nanofiller are dispersed in N-methylpyrrolidone, which is convenient for the polyamide resin to coat the nanofiller. The N-methylpyrrolidone also has good volatility and can gradually volatilize during the colloid curing process, so that the polyamide resin can form a coating layer. The polyamide resin has good compatibility with the epoxy resin matrix. After the polyamide coats the nanofiller, it can effectively protect the nanofiller and prevent it from agglomerating in the epoxy adhesive.
[0017] In a specific embodiment, the method for preparing the polyamide-coated nanofiller comprises the following steps:
[0018] dissolving a polyamide resin in N-methylpyrrolidone to form a polyamide solution;
[0019] The nanofiller is added into the polyamide solution, dispersed evenly, heated at 220-240° C. and 2.4-2.5 GHz microwave for 3-7 minutes, and then the solid and liquid are separated, and the solid is dried to obtain the polyamide-coated nanofiller.
[0020] By adopting the above technical solution, the present applicant found that the polyamide-coated nanofiller prepared under the above temperature and microwave conditions can further improve the mechanical strength and thermal conductivity of the epoxy adhesive. This may be because under the above conditions, the coating thickness of the polyamide is more appropriate.
[0021] In a specific embodiment, the nanofiller is any one of nanographite, nanocarbon black, and carbon nanotube.
[0022] By adopting the above technical solution and using the above specific nanofillers, an epoxy adhesive with good thermal conductivity can be prepared.
[0023] In a specific embodiment, the A component further includes polyacrylic acid.
[0024] By adopting the above technical solution, as a carboxylic acid compound, polyacrylic acid can provide additional reaction sites to react with hydroxyl groups or amine groups in epoxy resin to form a cross-linked network, which helps to improve the mechanical properties of epoxy adhesive.
[0025] In a second aspect, the present application provides a chip packaging method, which adopts the following technical solution:
[0026] A chip packaging method comprises the following steps:
[0027] The polyethylene glycol grafted epoxy resin, the polyamide coated nanofiller, the flame retardant, the diluent and the toughening agent are mixed evenly, and vacuumized to obtain component A; the epoxy curing agent and the curing accelerator are mixed evenly to obtain component B;
[0028] For the non-back-gold (back-silver) wafer, a thinning process is performed, and a DAF film is selected as a dicing film, and mechanical cutting is performed to obtain a chip;
[0029] The component A and the component B are mixed uniformly in a weight ratio of (5-6):1 to obtain a high thermal conductive epoxy adhesive for chip packaging, and the chip is attached to a carrier of a SOP lead frame using the high thermal conductive epoxy adhesive for chip packaging;
[0030] Aluminum wire is used for wire bonding, followed by plastic sealing, baking, marking, electroplating, rib cutting, forming and testing to complete the packaging.
[0031] In summary, this application has the following beneficial effects:
[0032] 1. The present application adopts polyethylene glycol grafted epoxy resin and polyamide coated nanofiller, which can improve the dispersibility of various components inside the epoxy adhesive for chip packaging, so that the epoxy adhesive has good thermal conductivity and mechanical properties, which helps to improve the chip packaging quality.
[0033] 2. The addition of polyacrylic acid in the present application can provide additional reaction sites to react with the hydroxyl or amine groups in the epoxy resin to form a cross-linked network, which helps to improve the mechanical properties of the epoxy adhesive.
[0034] 3. The method of the present application helps to improve chip packaging quality. DETAILED DESCRIPTION
[0035] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are purchased from the market. Among them, the brand of epoxy resin is E-44, the model of nanographite is LG-05, the brand of polyamide resin is DuPont 101L, the flame retardant is electronic grade high purity zinc borate (YL-0014); the diluent is dimethylformamide, the toughening agent is methyl acrylate, the nano carbon black is CABOT nano superconductive carbon black BP2000, and the carbon nanotube is Korean Kolon CN301C3.
[0036] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0037] Example
[0038] Example 1
[0039] This embodiment provides a high thermal conductivity epoxy adhesive for chip packaging, including component A and component B. Component A uses the following raw materials: 36g of polyethylene glycol grafted epoxy resin, 17.5g of polyamide-coated nanofiller, 5.5g of flame retardant, 3.5g of diluent, and 13.5g of toughening agent. Component B uses the following raw materials: 10g of epoxy curing agent and 0.75g of curing accelerator.
[0040] Polyethylene glycol grafted epoxy resin was prepared according to the following preparation method:
[0041] Weigh 20 g of epoxy resin, 7.5 g of polyethylene glycol, 1.5 g of an organotin catalyst and 45 g of acetone.
[0042] First, mix the epoxy resin and acetone, stir evenly, then add polyethylene glycol, heat to 70°C, stir evenly while keeping warm, then add an organic tin catalyst, and heat to 125°C while continuing to stir. The polyethylene glycol and epoxy resin undergo a ring-opening grafting reaction. After 8 hours of reaction, a polyethylene glycol-grafted epoxy resin is obtained.
[0043] The polyamide-coated nanofiller is prepared according to the following preparation method:
[0044] Weigh 12.5 g of nanographite, 12.5 g of polyamide resin, and 35 g of N-methylpyrrolidone.
[0045] dissolving a polyamide resin in N-methylpyrrolidone to form a polyamide solution;
[0046] The nanographite is added into the polyamide solution and dispersed uniformly. After heating at 230° C. and 2.45 GHz microwave for 5 minutes, the solution is centrifuged and the solid-liquid is separated. The solid is dried to obtain the polyamide-coated nanofiller.
[0047] This embodiment also provides a chip packaging method, which comprises the following steps:
[0048] According to the above ratio, polyethylene glycol grafted epoxy resin, polyamide coated nanofiller, flame retardant, diluent and toughening agent are mixed, stirred until uniform, vacuumed and bubbles are removed to obtain component A. Epoxy curing agent and curing accelerator are mixed uniformly to obtain component B.
[0049] For the non-back-gold (back-silver) wafer, a thinning process is performed, and a DAF film is selected as a dicing film, and a diamond blade is used for mechanical cutting to obtain a chip.
[0050] The components A and B are mixed evenly at a weight ratio of 5.5:1, and vacuumized to remove bubbles to obtain a high thermal conductive epoxy adhesive for chip packaging. The chip is pasted on a carrier of a SOP lead frame using the high thermal conductive epoxy adhesive for chip packaging.
[0051] Aluminum wire is used for wire bonding, followed by plastic sealing, baking, marking, electroplating, rib cutting, forming and testing to complete the packaging.
[0052] Example 2
[0053] The only difference between this embodiment and embodiment 1 is that component A uses the following raw materials: 28 g of polyethylene glycol-grafted epoxy resin, 20 g of polyamide-coated nanofiller, 4 g of flame retardant, 3 g of diluent, and 12 g of toughening agent.
[0054] Example 3
[0055] The only difference between this embodiment and embodiment 1 is that component A uses the following raw materials: 44 g of polyethylene glycol-grafted epoxy resin, 15 g of polyamide-coated nanofiller, 7 g of flame retardant, 4 g of diluent, and 15 g of toughening agent.
[0056] Example 4
[0057] The difference between this embodiment and embodiment 1 is that in the preparation method of polyethylene glycol grafted epoxy resin: 15 g of epoxy resin, 10 g of polyethylene glycol, 1 g of organic tin catalyst and 40 g of acetone are weighed.
[0058] Example 5
[0059] The difference between this embodiment and embodiment 1 is that in the preparation method of polyethylene glycol grafted epoxy resin: 25 g of epoxy resin, 5 g of polyethylene glycol, 2 g of organic tin catalyst and 50 g of acetone are weighed.
[0060] Example 6
[0061] The difference between this embodiment and embodiment 1 is that in the preparation method of polyethylene glycol grafted epoxy resin: first, epoxy resin and acetone are mixed, stirred evenly, polyethylene glycol is added, the temperature is raised to 60°C, stirred evenly while keeping warm, and then an organic tin catalyst is added. Under continuous stirring, the temperature is raised to 140°C, and the polyethylene glycol and epoxy resin undergo a ring-opening grafting reaction. After the reaction takes place for 7 hours, the polyethylene glycol grafted epoxy resin is obtained.
[0062] Example 7
[0063] The difference between this embodiment and embodiment 1 is that in the preparation method of polyethylene glycol grafted epoxy resin: first, epoxy resin and acetone are mixed, stirred evenly, polyethylene glycol is added, the temperature is raised to 80°C, stirred evenly while keeping warm, and then an organic tin catalyst is added. Under continuous stirring, the temperature is raised to 110°C, and the polyethylene glycol and epoxy resin undergo a ring-opening grafting reaction. After the reaction takes place for 9 hours, the polyethylene glycol grafted epoxy resin is obtained.
[0064] Example 8
[0065] The difference between this embodiment and embodiment 1 is that in the preparation method of the polyamide-coated nanofiller: 15 g of nanographite, 15 g of polyamide resin, and 30 g of N-methylpyrrolidone are weighed.
[0066] Example 9
[0067] The difference between this embodiment and embodiment 1 is that, in the preparation method of the polyamide-coated nanofiller: 10 g of nanographite, 10 g of polyamide resin, and 40 g of N-methylpyrrolidone are weighed.
[0068] Example 10
[0069] The only difference between this embodiment and embodiment 1 is that in the preparation method of the polyamide-coated nanofiller: nanographite is added to the polyamide solution and dispersed evenly, and after heating at 220° C. and 2.5 GHz microwave for 7 minutes, centrifugation and solid-liquid separation are performed, and the solid is dried to obtain the polyamide-coated nanofiller.
[0070] Embodiment 11
[0071] The only difference between this embodiment and embodiment 1 is that in the preparation method of the polyamide-coated nanofiller: nanographite is added to the polyamide solution and dispersed evenly, and after heating at 240°C and 2.4 GHz microwave for 3 minutes, centrifugation and solid-liquid separation are performed, and the solid is dried to obtain the polyamide-coated nanofiller.
[0072] Example 12
[0073] The difference between this embodiment and embodiment 1 is that in the preparation method of the polyamide-coated nanofiller: an equal amount of nano carbon black is used to replace nano graphite.
[0074] Embodiment 13
[0075] The difference between this embodiment and embodiment 1 is that in the preparation method of the polyamide-coated nanofiller: an equal amount of carbon nanotubes is used to replace nanographite.
[0076] Embodiment 14
[0077] The difference between this embodiment and embodiment 1 is that the A component uses the following raw materials: 36g of polyethylene glycol grafted epoxy resin, 17.5g of polyamide coated nanofiller, 5.5g of flame retardant, 3.5g of diluent, 13.5g of toughening agent, and 6.5g of polyacrylic acid. In the chip packaging method: polyethylene glycol grafted epoxy resin, polyamide coated nanofiller, flame retardant, diluent, polyacrylic acid and toughening agent are mixed, stirred until uniform, vacuumed, and bubbles are removed to obtain the A component.
[0078] Embodiment 15
[0079] The difference between this embodiment and embodiment 1 is that in the chip packaging method: component A and component B are mixed evenly at a weight ratio of 5:1, and vacuum is drawn to remove bubbles to obtain a high thermal conductive epoxy adhesive for chip packaging.
[0080] Example 16
[0081] The difference between this embodiment and embodiment 1 is that in the chip packaging method: component A and component B are mixed evenly at a weight ratio of 6:1, and vacuum is drawn to remove bubbles to obtain a high thermal conductive epoxy adhesive for chip packaging.
[0082] Comparative Example
[0083] Comparative Example 1
[0084] The only difference between this comparative example and Example 1 is that the polyethylene glycol grafted epoxy resin is replaced by an equal amount of epoxy resin.
[0085] Comparative Example 2
[0086] The only difference between this comparative example and Example 1 is that the polyamide-coated nanofiller is replaced by an equal amount of nanographite.
[0087] Performance testing
[0088] The following performance tests were performed on the high thermal conductivity epoxy adhesive for chip packaging prepared in Examples 1-16 and Comparative Examples 1-2:
[0089] According to the ASTM5470 test standard, the thermal conductivity of the epoxy adhesive is tested. According to the GB / T2570-1995 test standard, the bending strength of the epoxy adhesive is tested. The test results are shown in Table 1.
[0090] Table 1
[0091] Group Thermal conductivity W / (m·k) Bending strength / MPa Example 1 5.2 194 Example 2 5.7 186 Example 3 4.9 198 Example 4 5.3 190 Example 5 5.2 197 Example 6 5.2 188 Example 7 5.1 196 Example 8 5.6 189 Example 9 5.0 197 Example 10 5.3 192 Embodiment 11 5.2 190 Example 12 5.1 191 Embodiment 13 5.5 201 Embodiment 14 5.4 216 Embodiment 15 4.5 182 Example 16 5.9 218 Comparative Example 1 3.7 166 Comparative Example 2 3.9 168
[0092] Combining Example 1 and Comparative Examples 1-2 and Table 1, it can be seen that compared with Example 1, the thermal conductivity and bending strength of Comparative Examples 1-2 are reduced, which shows that the use of the raw material ratio and process of Example 1 is helpful to improve the thermal conductivity and mechanical properties of the epoxy adhesive, thereby improving the chip packaging quality.
[0093] Combining Examples 1-16 and Table 1, it can be seen that the thermal conductivity of Examples 1-16 is greater than 4.5 m·k, and the bending strength is greater than 180 MPa. The bending strength of Example 14 is greater, which shows that the ratio range and process condition range of Examples 1-16 are helpful to improve the thermal conductivity and mechanical properties of the epoxy adhesive, and adding polyacrylic acid to component A can further improve the mechanical properties of the epoxy adhesive.
[0094] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high thermal conductivity epoxy adhesive for chip packaging, characterized in that: The invention comprises a component A and a component B. Calculated by the total weight of the component A, the component A comprises the following raw materials in parts by weight: 28-44 parts of polyethylene glycol grafted epoxy resin, 15-20 parts of polyamide-coated nanofiller, 4-7 parts of flame retardant, 3-4 parts of diluent, and 12-15 parts of toughening agent. The component B comprises an epoxy curing agent and a curing accelerator in a weight ratio of 10:(0.5-1).
2. The high thermal conductivity epoxy adhesive for chip packaging according to claim 1, characterized in that: The polyethylene glycol grafted epoxy resin comprises the following raw materials: 15-25 parts of epoxy resin, 5-10 parts of polyethylene glycol, 1-2 parts of organic tin catalyst and 40-50 parts of acetone.
3. The high thermal conductivity epoxy adhesive for chip packaging according to claim 2, characterized in that: The preparation method of the polyethylene glycol grafted epoxy resin comprises the following steps: Weigh epoxy resin, polyethylene glycol, organotin catalyst and acetone according to proportion; First, epoxy resin and acetone are mixed, polyethylene glycol is added, and the mixture is stirred evenly at 60-80°C. An organic tin catalyst is added, and under continuous stirring at 110-140°C, the polyethylene glycol and epoxy resin undergo a ring-opening grafting reaction. After the reaction is completed, a polyethylene glycol-grafted epoxy resin is obtained.
4. The high thermal conductivity epoxy adhesive for chip packaging according to claim 1, characterized in that: The polyamide-coated nanofiller comprises the following raw materials: 10-15 parts of nanofiller, 10-15 parts of polyamide resin, and 30-40 parts of N-methylpyrrolidone.
5. The high thermal conductivity epoxy adhesive for chip packaging according to claim 4, characterized in that: The preparation method of the polyamide-coated nanofiller comprises the following steps: dissolving a polyamide resin in N-methylpyrrolidone to form a polyamide solution; The nanofiller is added into the polyamide solution, dispersed evenly, heated at 220-240° C. and 2.4-2.5 GHz microwave for 3-7 minutes, and then the solid and liquid are separated, and the solid is dried to obtain the polyamide-coated nanofiller.
6. The high thermal conductivity epoxy adhesive for chip packaging according to claim 4, characterized in that: The nano filler is any one of nano graphite, nano carbon black and carbon nano tube.
7. The high thermal conductive epoxy adhesive for chip packaging according to claim 1, characterized in that: The A component also includes polyacrylic acid.
8. A chip packaging method using the high thermal conductivity chip packaging epoxy adhesive according to any one of claims 1 to 7, characterized in that: The steps include: The polyethylene glycol grafted epoxy resin, the polyamide coated nanofiller, the flame retardant, the diluent and the toughening agent are mixed evenly, and vacuumized to obtain component A; the epoxy curing agent and the curing accelerator are mixed evenly to obtain component B; For the non-back-gold (back-silver) wafer, a thinning process is performed, and a DAF film is selected as a dicing film, and mechanical cutting is performed to obtain a chip; The component A and the component B are mixed uniformly in a weight ratio of (5-6):1 to obtain a high thermal conductive epoxy adhesive for chip packaging, and the chip is attached to a carrier of a SOP lead frame using the high thermal conductive epoxy adhesive for chip packaging; Aluminum wire is used for wire bonding, followed by plastic sealing, baking, marking, electroplating, rib cutting, forming and testing to complete the packaging.
Citation Information
Cited By
Heat-conducting adhesive, heat-conducting bonding layer and new energy automobile power battery comprising heat-conducting bonding layer
CN120888261A
Thermally conductive adhesive, thermally conductive adhesive layer and new energy automobile power battery comprising same
CN120888261B
Mobile phone narrow frame low-pressure injection molding sealing adhesive and preparation method thereof
CN121022321A